(untitled) (International Journal of Engineering and Computer Science, 2014)
Haptics is a recent enhancement to virtual environments allowing users “to touch” and feel the simulated objects they interact with. Current commercial products allow tactile feedback through desktop interfaces (such as the FEELIt mouse or the PHANToM arm) and force feedback at the fingertips through haptic gloves (such as the CyberTouch and the CyberGrasp). Haptics is a recent enhancement to virtual environments allowing users “to touch” and feel the simulated objects they interact with. Current commercial products allow tactile feedback through desktop interfaces (such as the FEELIt mouse or the PHANToM arm) and force feedback at the fingertips through haptic gloves (such as the CyberTouch and the CyberGrasp)., etc. It is at present difficult to simulate complex virtual environments that have a realistic behavior. This task is added by the recent introduction of haptic toolkits. The simulation of natural phenomenon is an important goal for this technology. Current systems may not be able to generate forces with the speed required to simulate real world situations. Accurate and high-speed devices must be perfected in order to create real-world simulations